2014
DOI: 10.1016/j.cell.2014.03.049
|View full text |Cite
|
Sign up to set email alerts
|

CLP1 Founder Mutation Links tRNA Splicing and Maturation to Cerebellar Development and Neurodegeneration

Abstract: SUMMARY Neurodegenerative diseases can occur so early as to affect neurodevelopment. From a cohort of over 2000 consanguineous families with childhood neurological disease, we identified a founder mutation in four independent pedigrees in cleavage and polyadenylation factor I subunit (CLP1). CLP1 is a multifunctional kinase implicated in tRNA, mRNA and siRNA maturation. Kinase activity of the CLP1 mutant protein was defective, and the tRNA endonuclease complex (TSEN) was destabilized, resulting in impaired pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
271
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(283 citation statements)
references
References 47 publications
8
271
0
4
Order By: Relevance
“…Schaffer et al 2014). Although reported previously to be expressed ubiquitously (Thisse and Thisse 2004), in situ hybridization of rpl10 riboprobes in 2 dpf embryos demonstrated enriched expression in the anterior vs. posterior structures, particularly at the midbrain-hindbrain boundary ( Figure S1).…”
Section: Resultsmentioning
confidence: 73%
“…Schaffer et al 2014). Although reported previously to be expressed ubiquitously (Thisse and Thisse 2004), in situ hybridization of rpl10 riboprobes in 2 dpf embryos demonstrated enriched expression in the anterior vs. posterior structures, particularly at the midbrain-hindbrain boundary ( Figure S1).…”
Section: Resultsmentioning
confidence: 73%
“…In the second, hClp1, a component of the mammalian SEN complex, catalyzes phosphorylation of the 59 end of the 39 exon of tRNAs, although the ligase is not identified (Zillmann et al 1991;Weitzer and Martinez 2007;Ramirez et al 2008). New studies reported that CLP1 mutation leads to severe neurodegenerative disease, and fibroblasts from human patients accumulate linear introns with a 59 hydroxyl, although intron accumulation was not observed in in vitro analyses (Karaca et al 2014;Schaffer et al 2014). We wonder whether introns are targets of CLP1 in vertebrate cells and whether it is possible that defects in tRNA intron turnover might contribute to the neurological phenotypes caused by CLP1 mutations.…”
Section: The Trna Ligase Rlg1 Phosphorylates Trna Introns Prior To Dementioning
confidence: 99%
“…Patient-derived neurons displayed both depletion of mature tRNAs and accumulation of unspliced pre-tRNAs. Transfection of partially processed tRNA fragments into patient cells exacerbated oxidative stress-induced cell death (76). The biogenesis of these tRNA fragments is distinct from that of ANG-induced tiRNAs; however, collective findings in the field suggest that tRNA metabolism and development of neurodegenerative diseases are strongly related.…”
Section: Role Of Tirnas In Neurons: Implications For Neurodegenerativmentioning
confidence: 99%